Nemo-like kinase reduces mutant huntingtin levels and mitigates Huntington's disease. (2nd April 2020) - Jiang, Mali; Zhang, Xiaoyan; Liu, Hongshuai; LeBron, Jared; Alexandris, Athanasios; Peng, Qi; Gu, Hao; Yang, Fanghan; Li, Yuchen; Wang, Ruiling; Hou, Zhipeng; Arbez, Nicolas; et al.
Abstract: Nemo-like kinase (NLK), an evolutionarily conserved serine/threonine kinase, is highly expressed in the brain, but its function in the adult brain remains not well understood. In this study, we identify NLK as an interactor of huntingtin protein (HTT). We report that NLK levels are significantly decreased in HD human brain and HD models. Importantly, overexpression of NLK in the striatum attenuates brain atrophy, preserves striatal DARPP32 levels and reduces mutant HTT (mHTT) aggregation in HD mice. In contrast, genetic reduction of NLK exacerbates brain atrophy and loss of DARPP32 in HD mice. Moreover, we demonstrate that NLK lowers mHTT levels in a kinase activity-dependent manner, while having no significant effect on normal HTT protein levels in mouse striatal cells, human cells and HD mouse models. The NLK-mediated lowering of mHTT is associated with enhanced phosphorylation of mHTT. Phosphorylation defective mutation of serine at amino acid 120 (S120) abolishes the mHTT-lowering effect of NLK, suggesting that S120 phosphorylation is an important step in the NLK-mediated lowering of mHTT. A further mechanistic study suggests that NLK promotes mHTT ubiquitination and degradation via the proteasome pathway. Taken together, our results indicate a protective role of NLK in HD and reveal a new molecular target to reduce mHTT levels.